DFI funding and infrastructure development In South Africa: A case of under resourced schools in Northern Cape - Jack, Jonita Phatheka (Graduate School of Business (GSB), 2025)
This study investigated the role of Development Finance Institutions (DFIs) in addressing infrastructure deficits in under-resourced schools in the Northern Cape, South Africa, and their impact on educational performance. The research problem is centred on the persistent lack of adequate infrastructure in schools, which hinders access to quality education and exacerbates educational inequalities. The study sought to explore how DFI-funded infrastructure projects contribute to improving the physical learning environment, access to educational materials, and the long-term sustainability of educational development in disadvantaged areas. The research employed a qualitative approach, utilizing in-depth interviews with key stakeholders, including school administrators, government officials, and DFI representatives. Additionally, a qualitative analysis of financial data was conducted to assess the allocation and impact of DFI funding. This methodological approach provided a comprehensive understanding of the mechanisms through which DFIs influence educational infrastructure and the factors that affect the effectiveness of their interventions. The findings of the study revealed that DFIs have made significant contributions to enhancing the physical infrastructure of under-resourced schools. Key outcomes included the construction of new classrooms, libraries, and laboratories, as well as the renovation of existing facilities. DFI funding also improved access to essential educational materials, such as textbooks, digital tools, and e-learning platforms, thereby enriching the learning environment. The study also highlighted the importance of future-oriented strategies to ensure sustainable infrastructure development, particularly considering technological advancements and the need for inclusive education that caters to diverse learner needs. The conclusions of the study underscored the need for improved accountability, streamlined procedures, and stronger collaboration among DFIs, government bodies, and local communities to ensure long-term sustainability of infrastructure projects in South Africa's education sector. It offers policy recommendations and suggests future research on learner outcomes and community engagement. This research provides valuable insights for policymakers, educators, and development practitioners seeking to address infrastructure challenges in South Africa's education sector.